Environmental Protection and Transitions from Conflict to Peace Clarifying Norms, Principles, and Practices - Stahn, Carsten; Iverson, Jens; S. Easterday, Jennifer (Oxford University Press, 2017)
This book is the first targeted work in the legal literature that investigates environmental challenges in the aftermath of conflict. The volume brings together academics, policy-makers, and practitioners from different disciplines to clarify policies and practices of environmental protection and key legal considerations related to normative frameworks (e.g. international environmental law, international humanitarian law, transitional justice, and human rights), the treatment of substantive principles (e.g. proportionality under jus in bello and jus post bellum, environmental integrity), 'shared responsibility', and accountability mechanisms for environmental damage. By providing a comprehensive and in-depth analysis of environmental protection and natural resource management during the transition to peace, the volume reveals strong links between the peace-orientation of jus post bellum and environmental principles, such as intergenerational equity and precaution. There is a great deal of work to do to ensure greater protection of the environment before, during, and after conflict. It remains a challenge to align protection with the political interest of states, and the increasing involvement of non-state actors in armed conflict. This volume marks a starting point for an urgently needed space for states, international organizations, and civil society to discuss, and debate conflict and the environment. By engaging with the International Law Commission's 2016 Draft Principles on the Protection of the Environment in Relation to Armed Conflicts, the volume adds clarity to the law and momentum to the development of the law in this important area.